Transition from fossil fuels to renewable energy: Evidence from a dynamic simulation model with endogenous resource substitution - Ujjayant Chakravorty; Kin-ping Tse (Fondazione Eni Enrico Mattei (FEEM), 1999)
This paper applies an economic model of climate change that is based on endogenous substitution of energy resources to determine the effect of advances in renewable technology on aggregate and sectoral fossil fuel use and energy prices. It uses a Nordhaus type partial equilibrium model of the energy sector with four demand sectors - electricity, transportation, residential and industrial energy and three of the commercially most important exhaustible resources - oil, coal and natural gas. The findings suggest that among the major commercial fuels, oil and natural gas use are not very sensitive to changes in the cost of solar energy, while coal use is expected to reduce drastically as solar becomes more economical. These results suggest that research and development in renewable energy may play only a limited role in the short run, while creating the basis for a transition to a sustainable energy economy over the longer time horizon.
Keywords: Q30; Q42; O30; 330; Exhaustible resources; endogenous substitution; alternative energy sources; Klimawandel; Energiesubstitution; Fossile Energie; Sonnenenergie; Energie; Preis; Partielles Gleichgewicht; Welt